CONFLICTS BETWEEN COMMERCIAL AND SCIENTIFIC INTERESTS IN PHARMACEUTICAL ADVERTISING FOR MEDICAL JOURNALS - Tsai, Alexander C. (2003)
In 1992, researchers from the University of California-Los Angeles published a study on the scientific merit and validity of pharmaceutical advertisements in medical journals. Their results led them to conclude, provocatively, that many pharmaceutical advertisements contained deficiencies in areas in which the U.S. Food and Drug Administration had established explicit standards of quality. This article provides a detailed account of third-party reactions to the study following its publication in the Annals of Internal Medicine, as well as the implications for those involved, including the authors, editors, and publisher. The increasingly diverging interests between medical journal editors and publishers are also discussed and highlighted by two recent cases of editors’ departures from prominent general-interest medical journals.